równanie na teraz plssss[tex]\frac{3-2x}{6} = \frac{2}{3}[/tex]

Odpowiedź :

Odpowiedź:

3-2x  /6= 2/3

  3( 3-2x)= 6*2

 9-6x =12

  -6x= 12-  9

    -6x= 3 /:6

   x= -1/2

spr...   3 - 2*(-1/2)  /6= 2/3

   3+ 1 /6= 2/3

       4/6= 2/3

          2/3=2/3

       L=P

Szczegółowe wyjaśnienie:

Odpowiedź:

Szczegółowe wyjaśnienie:

(3 - 2x)/6 = ⅔ /*6

3- 2x = 6 * ⅔

3- 2x = 12/3

3 - 2x = 4

- 2x = 4 - 3

- 2x = 1 /:(-2)

x = - ½

Spr :

L = [ (3 - 2 * (-½)] : 6 = (3 + 1) : 6 = 4/6 = ⅔

P = ⅔

L = P

Viz Inne Pytanie